Structural Correlates of Reading the Mind in the Eyes in Autism Spectrum Disorder - Sato, Wataru; Uono, Shota; Kochiyama, Takanori; Yoshimura, Sayaka; Sawada, Reiko; Kubota, Yasutaka; Sakihama, Morimitsu; Toichi, Motomi (Frontiers in Human Neuroscience, 2017)
Behavioral studies have shown that individuals with autism spectrum disorder (ASD) have impaired ability to read the mind in the eyes. Although this impairment is central to their social malfunctioning, its structural neural correlates remain unclear. To investigate this issue, we assessed Reading the Mind in the Eyes Test, revised version (Eyes Test) and acquired structural magnetic resonance images in adults with high-functioning ASD (n = 19) and age-, sex-, and intelligence quotient-matched typically developing controls (n = 19). On the behavioral level, the Eyes Test scores were lower in the ASD group than in the control group. On the neural level, an interaction between group and Eyes Test score was found in the left temporoparietal junction (TPJ). A positive association between the Eyes Test score and gray matter volume of this region was evident in the control group, but not in the ASD group. This finding suggests that the failure to develop appropriate structural neural representations in the TPJ may underlie the impaired ability of individuals with ASD to read the mind in the eyes. These behavioral and neural findings provide support for the theories that impairments in processing eyes and the ability to infer others’ mental states are the core symptoms of ASD, and that atypical features in the social brain network underlie such impairments.